Global Commitments to Conserving and Monitoring Genetic Diversity Are Now Necessary and Feasible. (26th May 2021) - Hoban, Sean; Bruford, Michael W; Funk, W Chris; Galbusera, Peter; Griffith, M Patrick; Grueber, Catherine E; Heuertz, Myriam; Hunter, Margaret E; Hvilsom, Christina; Stroil, Belma Kalamujic; Kershaw, Francine; Khoury, Colin K; et al.
Abstract: Global conservation policy and action have largely neglected protecting and monitoring genetic diversity—one of the three main pillars of biodiversity. Genetic diversity (diversity within species) underlies species' adaptation and survival, ecosystem resilience, and societal innovation. The low priority given to genetic diversity has largely been due to knowledge gaps in key areas, including the importance of genetic diversity and the trends in genetic diversity change; the perceived high expense and low availability and the scattered nature of genetic data; and complicated concepts and information that are inaccessible to policymakers. However, numerous recent advances in knowledge, technology, databases, practice, and capacity have now set the stage for better integration of genetic diversity in policy instruments and conservation efforts. We review these developments and explore how they can support improved consideration of genetic diversity in global conservation policy commitments and enable countries to monitor, report on, and take action to maintain or restore genetic diversity.